Условия уменьшения шероховатости поверхности отверстия для разных методов абразивной обработки - Новиков, Федор Васильевич; Рябенков, Игорь Александрович (НТУ "ХПИ", 2016)
Аналитически обоснованы условия уменьшения шероховатости поверхности отверстия при абразивной обработке, которые состоят в обеспечении одновысотного выступания зерен на рабочей поверхности абразивного инструмента и увеличении их количества. Это достигается применением доводки свободным абразивом, а также шлифованием кругами с примерно одновысотным выступанием зерен над уровнем связки, изменением оси вращения круга – она должна быть направлена перпендикулярно оси вращения обрабатываемой детали.

Analytically substantiated conditions reduce the roughness of the surface of the holes at different methods of abrasion. It is found that the internal grinding, as a method of finishing high-holes does not provide a surface roughness at Ra = 0,05 mm, due to different height location of abrasive grains on the working surface of the wheel and a small amount of participating in the forming surfaces. The conditions for a substantial reduction of surface roughness by the use of deep grinding with a relatively low speed of rotation of the details, as well as through the creation of platforms on the tops of the grain. Calculations revealed that provision of protrusion odnovysotnogo grains on the working surface of the abrasive tool and increase in the number of grains participating in the formation of surface roughness are the basic conditions of surface roughness reduction when abraded. Run these conditions can be using free abrasive polishing and grinding abrasive wheels with approximately odnovysotnym protruding grains above the ligament, which is achieved, for example, a change in the axis of rotation of the grinding wheel – it should be directed perpendicular to the axis of rotation of the workpiece.
Terms reduce the roughness of the surface of the holes at different methods of abrasion
Keywords: шероховатость поверхности; отверстие; абразивная обработка; внутреннее шлифование; глубинное шлифование; доводка свободным абразивом; абразивные зерна; разновысотное расположение; абразивный круг; surface roughness; hole; abrasive machining; internal grinding; creep feed grinding; lapping with a free abrasive; location of abrasive grains; abrasive wheel